Learning English Through Linguistic and Musical Intelligences - Nila Sari Dewi; Zoltan Kodaly (Bandar Lampung University (UBL), 2013)
The objective of this research was to describe; (1). the process of learning English by using English songs video as media, (3). the system of learning evaluation , and (4). the improvement of students’ vocabulary learning achievement.The methodology of this research was Classroom Action Research that involved students of Foreign Language Academy Dian CiptaCendikia Bandar Lampung for D3-BI-IA class and D3-BI-IB class in period 2011/2012. The subject was Vocabulary Building. This action research consisted of 2 cycles. The first cycle, students did activities such as listening to the song in audio, reading the lyrics of song, understanding the words meaning, and selecting the function of words in the sentences. The second cycle, students did activities as listening to the song and doing the task (cloze procedure), reading the text of song through audio visual, understanding sentences’ meanings, producing sentence and retelling the content of song. The instruments of research were observation and test.The research findings indicated that; (1) there were improvement of active students in learning activities, that was; D3-BI-IA class, in the first cycle, the first meeting had 12 students or 60% and the second meeting had 14 students or 70%, and in the second cycle, the first meeting had 14 students or 70% and the second meeting had 18 students or 90%. Meanwhile, D3-BI-IB class, in the first cycle, the first meeting had 10 students or 50%, and the second meeting had 13 students or 65 %, and in the second cycle, the first meeting had 14 students or 70%, and the second meeting had 17 students or 85%, (3). The learning evaluation used Simpel PAS (Program AnalisisSoal). In the first cycle, the test validity was 0,2 (low), the test reliability was was 0,59 (moderate), the level of difficulty was 0,54(moderate) and the discrimination power was 0,36 (moderate). In the second cycle, the test validity was 0,41 (moderate), the test reliability was o,78 (high), the level of difficulty was 0,68 (moderate) and the discrimination power was 0,36 (moderate), (4). the achievement of vocabulary mastery in the first cycle, students of D3-BI-IA class who passed the test were 10 students or 50% and D3-BI-IB class was 12 students or 60%. The second cycle, students of D3-BI-IA class who passed the test were 16 students or 80%, and D3-BI-IB class was 16 students or 80%.